The use of singlish in the mass media - Lee, Liane (2014)
Singlish is a term coined only in the eighties to represent a Singaporean version of the English language. Despite its pervasive use in our daily lives, its recent appearance in the mass media sparked off conflicting arguments with regard to its desirability.